Analysis Of Natural Tourism Of Anambas Island Riau Islands - Muhammad Nazel SP; Dhiya Hasna LN (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
The Anambas Islands are small islands in Indonesia, which are located in the South China Sea. The Anambas Islands are also part of the Riau Archipelago Province, which is surrounded by many small islands, most of which are uninhabited but still have pristine natural beauty. The aim of this research is to analyze community empowerment in community-based tourism development and develop a strategy for developing community-based tourism development to increase local revenue. Tourism supporting infrastructure that must be improved in the development of tourism development in Anambas Islands Regency is improving public infrastructure and infrastructure in the tourism sector, namely sea transportation and marine tourism recreation facilities which have the highest value of 4.93, meaning that they must be focused more on their development. The method we take is qualitative and the internet is the main means we use to get a lot of information about the advantages and disadvantages of some of the islands in the Anambas Archipelago. The results of this research show the opportunity to build new tourism works to exploit its beautiful nature and of course build cooperation between local communities in the Anambas Islands.